2017
DOI: 10.1159/000475570
|View full text |Cite
|
Sign up to set email alerts
|

A MicroRNA-124 Polymorphism is Associated with Fracture Healing via Modulating BMP6 Expression

Abstract: Background: miR-124-3p has been reported to be involved in the pathogenesis of many diseases by modulating a variety of signaling pathways. In this study, we aimed to understand the impact of miR-124-3p expression level on the fracture healing in the patients of metaphyseal fracture of distal tibia, who received minimal invasive percutaneous plate osteosynthesis. Methods: We firstly collected 195 patients of metaphyseal fracture of distal tibia, and the genotype of rs531564 was determined: GG (n=124) and GC+CC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 33 publications
0
22
1
Order By: Relevance
“…More importantly, BMP‐6 mRNA and protein expression levels were significantly decreased in the GG group compared with GC and CC groups, confirming a negative regulatory relationship between miR‐124‐3p and BMP‐6. The results suggest that the rs531564 miRNA‐124‐3p polymorphism may serve as a biomarker for metaphyseal distal tibia fractures …”
Section: Mirna Polymorphisms and Human Fracturesmentioning
confidence: 96%
See 2 more Smart Citations
“…More importantly, BMP‐6 mRNA and protein expression levels were significantly decreased in the GG group compared with GC and CC groups, confirming a negative regulatory relationship between miR‐124‐3p and BMP‐6. The results suggest that the rs531564 miRNA‐124‐3p polymorphism may serve as a biomarker for metaphyseal distal tibia fractures …”
Section: Mirna Polymorphisms and Human Fracturesmentioning
confidence: 96%
“…In addition to profiling studies, researchers have begun to report on the association of miRNA polymorphisms with clinical fractures. For example, one study focused on the effect of miR‐124‐3p expression levels in 195 patients with metaphyseal fractures of the distal tibia . Specifically, the study investigated the presence of the genotype of rs531564 (a single‐nucleotide polymorphism [SNP], site in pri‐miR‐124) by dividing the patients into two groups by the genotypes, GG ( n = 124) and GC + CC ( n = 71), and found that miR‐124‐3p expression was significantly increased in the GG group compared with the GC and CC groups.…”
Section: Mirna Polymorphisms and Human Fracturesmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction of TGF-βs/BMPs with TGF-β specific type 1 and type 2 or BMP serine/threonine kinase receptors initiates the signaling cascade via canonical (or Smad-dependent pathways) and non-canonical pathways (or Smad-independent signaling pathways) [50]. The TGF-β/BMP signaling pathway plays an important regulatory role in bone repair [51-56]. It is also confirmed to be involved in PEMF-induced osteogenesis.…”
Section: Underlying Signaling Pathwaysmentioning
confidence: 99%
“…The migration and osteogenic differentiation of BMSCs are tightly regulated by various cellular signals [3][4][5][6][7][8], and in vitro and in vivo studies have shown that bone morphogenetic proteins (BMPs) play a critical role in osteogenic differentiation and bone formation [9][10][11]. BMPs combine with type I and II receptors on the cell surface to form a complex and activate the Smad signalling pathways, which regulate osteogenic gene expression [12,13], suggesting that manipulation of BMP signalling may be employed as a therapeutic approach to treat bone nonunion. However, this technique has several key disadvantages, as these factors must be used at supraphysiological concentrations, are shortlived and expensive, and result in many side effects [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%